Intravenous lidocaine infusions for 48 hours in open colorectal surgery: a prospective, randomized, double-blinded, placebo-controlled trial - Matthew Liang Jinn Ho; Stephen John Kerr; Jennifer Stevens (Korean Journal of Anesthesiology, 2018)
BackgroundAlthough intravenous (i.v.) lidocaine is used as a perioperative analgesic in abdominal surgery, evidence of efficacy is limited. The infusion dose and duration remain unclear. This study aimed to investigate the effect of a longer low-dose 48-hour infusion regimen on these outcomes.MethodsFifty-eight adults undergoing elective open colorectal surgery were randomized into the lidocaine group (1.5 mg/kg bolus followed by 1 mg/kg/h infusion for 48 hours) and control group. After surgery, patients were given a fentanyl patient-controlled analgesia machine and time to first bowel movement (primary outcome) and flatus were recorded. Postoperative pain scores and fentanyl consumption were assessed for 72 hours.ResultsThere was no significant difference in time to first bowel movement (80.1 ± 42.2 vs. 82.5 ± 40.4 hours; P = 0.830), time to first flatus (64.7 ± 38.5 vs. 70.0 ± 31.2 hours; P = 0.568), length of hospital stay (9 [8–13] vs. 11 [9–14) days; P = 0.531], nor postoperative pain scores in the lidocaine vs. control groups. Cumulative opioid consumption was significantly lower in the lidocaine vs. the control group from 24 hours onwards. At 72 hours, cumulative opioid consumption (µg fentanyl) in the lidocaine group (1,570 [825–3,587]) was over 40% lower than in the placebo group (2,730 [1,778–5,327]; P = 0.039).ConclusionsA 48-hour low-dose i.v. lidocaine infusion does not significantly speed the return of bowel function in patients undergoing elective open colorectal surgery. It was associated with reduced postoperative opioid consumption, but not with earlier hospital discharge, or lower pain scores.